CD73‐generated extracellular adenosine promotes resolution of neutrophil‐mediated tissue injury and restrains metaplasia in pancreatitis. Issue 1 (5th December 2022) - O'Brien, Baylee J.; Faraoni, Erika Y.; Strickland, Lincoln N.; Ma, Zhibo; Mota, Victoria; Mota, Samantha; Chen, Xuebo; Mills, Tingting; Eltzschig, Holger K.; DelGiorno, Kathleen E.; Bailey‐Lundberg, Jennifer M.
Abstract: Pancreatitis is currently the leading cause of gastrointestinal hospitalizations in the US. This condition occurs in response to abdominal injury, gallstones, chronic alcohol consumption or, less frequently, the cause remains idiopathic. CD73 is a cell surface ecto‐5′‐nucleotidase that generates extracellular adenosine, which can contribute to resolution of inflammation by binding adenosine receptors on infiltrating immune cells. We hypothesized genetic deletion of CD73 would result in more severe pancreatitis due to decreased generation of extracellular adenosine. CD73 knockout ( CD73 −/− ) and C57BL/6 (wild type, WT) mice were used to evaluate the progression and response of caerulein‐induced acute and chronic pancreatitis. In response to caerulein‐mediated chronic or acute pancreatitis, WT mice display resolution of pancreatitis at earlier timepoints than CD73 −/− mice. Using immunohistochemistry and analysis of single‐cell RNA‐seq (scRNA‐seq) data, we determined CD73 localization in chronic pancreatitis is primarily observed in mucin/ductal cell populations and immune cells. In murine pancreata challenged with caerulein to induce acute pancreatitis, we compared CD73 −/− to WT mice and observed a significant infiltration of Ly6G+, MPO+, and Granzyme B+ cells in CD73 −/− compared to WT pancreata and we quantified a significant increase in acinar‐to‐ductal metaplasia demonstrating sustained metaplasia and inflammation in CD73 −/− mice. Using neutrophil depletion in CD73 −/− mice, we show neutrophil depletion significantly reduces metaplasia defined by CK19+ cells per field and significantly reduces acute pancreatitis. These data identify CD73 enhancers as a potential therapeutic strategy for patients with acute and chronic pancreatitis as adenosine generation and activation of adenosine receptors is critical to resolve persistent inflammation in the pancreas.